PS 08-71 UTILITY OF HEMODYNAMIC EVALUATION FOR PATHOPHYSIOLOGICAL INTERPRETATION IN ORTHOSTATIC UPRIGHT POSTURAL BLOOD PRESSURE CHANGES. (September 2016) - Schiavone, Maximo; Gonzalez, Sergio; Martinez, Guillermo; Rincon, Daniel; La Greca, Rodolfo; Inserra, Felipe; Ramella, Irma
Abstract : Objective: 1- Analyze whether the increases / decreases of blood pressure by standing are associated with characteristic resting hemodynamic profiles. 2- Establish whether such orthostatic upright postural blood pressure changes are associated with specific hemodynamic changes by standing. Design and Method: 301 patients were included (age: 57, 6 ± 13, 52 years). The following variables were analyzed: Systolic blood pressure (SBP), heart rate (HR), stroke volume (SV), systemic vascular resistance (SVR), arterial compliance (AC) and thoracic fluid content (TFC) with impedance cardiography in supine position and after the third minute of standing. Three groups were defined acording to the types of responses of SBP when standing: decrease (DES), stabilization (EST) and increase (INC) according to ± 1SD of the mean of delta-SBP (standing-lying). Results: There were 40 patients in DES, 225 in EST and 36 patients in INC group. Anthropometric variables, sex, underlying diseases and medications showed homogeneous distributions in the 3 groups (p > 0.05). The DES group presented at supine position higher SVR and SBP, with lower levels of SV and AC regarding EST-INC groups (DS p < 0.05, SBP, SVR and AC p < 0.001). The INC group had higher SV at rest than EST-DES groups (p < 0.05 for both). By standing the DES group showed smaller increases in SVR regarding EST-INC groups (p = 0.05 and p = 0.03, respectively). The INC group, however, showed a bigger increase of delta-SVR compared to the EST-DES groups (p < 0.001 for both). Conclusions: Hemodynamic differences were evident features to the profile of variation in SBP during standing. Patients with DES showed a hypodynamic profile (low SV-high SVR) with lower increase in SVR by standing. INC group presented a hyperdynamic baseline trend, with a greater increase in SVR by standing.Specific therapeutics could help improve the neuro-cardiovascular adjustment in these patients.